Environmental application of quartz‑based construction waste: tartrazine removal from aqueous media - Torres Perez, Jonatan (2021)
The sorption of tartrazine, also called yellow number 5 dye, by a construction waste (natural quartz), homoionized with sodium and modified with a cationic surfactant was tested. The adsorbent materials were characterized by FTIR, SEM, EDX and DRX. The effect of contact time, pH (3, 6 and 9) and temperature (25, 35 and 65 °C) on the tartrazine dye removal were evaluated. Sorption kinetic parameters were obtained by using the pseudo-first-order, pseudo-second-order and Elovich models. The maximal sorption capacity was analysed by Freundlich, Langmuir, and Temkin isotherm models. It was found that the pseudo-first-order kinetic model fits well with the experimental data (R > 0.98) from the sorption process onto modified quartz. The Freundlich isotherm fitted in the best way the sorption data (R = 0.9377). The sorption capacities of natural quartz, sodium quartz, and modified quartz for tartrazine were 0.09, 1.12 and 14.72 mg/g, respectively. Modified quartz can be a cheap, useful, and innovative sustainable adsorbent material for the removal of tartrazine from aqueous solutions.